MULTIPLE TAXATION AND PROFITABILITY OF SELECTED SMALL SCALE BUSINESS IN TARABA STATE, NIGERIA - Bello, Sanusi (International Journal For Research In Business, Management And Accounting, 2020)
This paper examined Multiple Taxation and Profitability of Small Scale Business in Taraba State, Nigeria., It is presumed that small scale businesses are faced with payment of multiple taxes, incessant high and arbitrary charges, and inadequate provision of essential amenities that could foster the progress of the business, non-proper registration and assessment of businesses before levying tax by the tax authorities. A survey design was adopted and the respondents were 98 involving the entrepreneurs and staff sampled from the fifteen (15) bread bakeries in Jalingo metropolis. Random sampling was used in selecting the respondents. The modified Linkert’s pattern of data measurement was adopted. Questionnaires were administered on the two samples of respondents namely: entrepreneurs and their employees. Data were collected, tabulated and analyzed using descriptive statistics. One hypothesis was tested using standard deviation to test the influence of multiple taxes on profitability of bread bakeries. It was discovered that multiple taxes negatively affect profitability of small scale business. Small scale business is a major tool for accelerated economic development of any nation and tax is supposed to therefore contribute to the development of the country; yet, small scale businesses pay multiple taxes which at the long run significantly affect their profitability. Tax authorities are equally expected to demonstrate the principles of equity, convenience and economy in tax collection. It was recommended that tax authorities should ensure proper documentation, computation of profits before assessing businesses for payment and laws governing taxation of small scale businesses should be revisited to ensure that multiple taxation is minimized or even eradicated so that small scale businesses could continue to remain in business for the purpose of national development. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />